Case Report of Autoimmune Hepatitis from a Tertiary Centre in Bangladesh - Al-Mahtab, Mamun; Rahman, Salimur; Shrestha, Ananta; Kamal, Md; Khan, Mobin; Huq, AKM Faizul; Barua, Uttam Kumar (Bangladesh Liver Journal, 2009)
Autoimmune hepatitis is defined as chronic liver disease of unknown aetiology with aberrant autoreactivity and genetic predisposition, characterized by female predominance, circulating auto-antibodies, hypergammaglobulinaemia and association with HLA DR3 and HLA DR4 [1]. We present two patients with autoimmune. The first patient is a young lady who was diagnosed with autoimmune chronic hepatitis. The second patient, on the other hand, is an elderly gentleman who presented to us with autoimmune hepatitis related decompensated cirrhosis of liver. doi: 10.3329/blj.v1i1.2652 Bangladesh Liver Journal Vol.1(1) 2009 p.53-54